UNA APROXIMACION A LA HISTORIA DE LAS IDEAS FILOSOFICAS EN MEXICO. SIGLO XIX Y PRINCIPIOS DEL XX - Rovira Gaspar, María del Carmen (coordinación); Aceves Gómez, Emma Luz (autor) (1997)
INCLUYE BIBLIOGRAFIA